The Influence of Demographics Factor on Pension Planning and Financial Literacy of Private Employee - Maria Rycca P. Sembiring; Farah Margaretha Leon (Business and Entrepreneurial Review, 2021)
The purpose of this research is to analyze the relationships of demographics factors to pension planning and financial literacy. The research methodology used in this research is the quantitative method. The sample in this research is private employees that are determined by using sampling probability. The data analysis method in this research is a correlation test that used the Chi-Square approach. The result and contribution in this research is there any correlation between demographics factor and pension planning. From the demographics factor in this research can be seen that education factor, marriage status, and income have its significant relationship with pension planning. On the other hand, gender factor and age have no relationship to pension planning. From demographics factor in this research concluded that age, education level, marital status, and income has a significant relationship to financial literacy. Whereas, gender factor has no relationship to financial literacy.